Musical Sincerity and Transcendence in Film : Reflexive Fictions - Cochran, Timothy B. (Ashgate screen music series, 2023)
Examining a wide range of movies from the last thirty-five years, Timothy Cochran traces two recurring assumptions implied by self-conscious music-making in recent cinema: that music is a potent means of expressing sincerity and experiencing humanistic depth, and that music can provide varied forms of transcendence and psychological escape.